2022
DOI: 10.1002/ajh.26709
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of jaktinib in the treatment of Janus kinase inhibitor‐naïve patients with myelofibrosis: Results of a phase II trial

Abstract: Myelofibrosis (MF) is associated with several constitutional symptoms. Currently, there are few therapeutic options for MF. Jaktinib, a novel, small-molecule inhibitor of JAK, is currently being studied for its potential to treat MF. This phase 2 trial investigated efficacy and safety of jaktinib in the treatment of MF patients. The primary end point was the proportion of patients with ≥35% reduction in spleen volume (SVR35, proportion of patients with ≥35% reduction in spleen volume) at week 24. The secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…Similar results were obtained in an updated analysis from the open‐label phase of the MOMENTUM study, in which all patients received momelotinib, and loss of transfusion independence was documented in 10% and 23% of momelotinib and danazol randomized patients, respectively 22 . Furthermore, a phase 2 study with Jaktinib, a deuterated compound of momelotinib, revealed anemia response rate of 36% in patients with a baseline hemoglobin level ≤10 g/dl, with 2 of 6 transfusion‐dependent patients becoming transfusion‐independent after treatment 23,24 …”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Similar results were obtained in an updated analysis from the open‐label phase of the MOMENTUM study, in which all patients received momelotinib, and loss of transfusion independence was documented in 10% and 23% of momelotinib and danazol randomized patients, respectively 22 . Furthermore, a phase 2 study with Jaktinib, a deuterated compound of momelotinib, revealed anemia response rate of 36% in patients with a baseline hemoglobin level ≤10 g/dl, with 2 of 6 transfusion‐dependent patients becoming transfusion‐independent after treatment 23,24 …”
Section: Discussionsupporting
confidence: 65%
“…22 Furthermore, a phase 2 study with Jaktinib, a deuterated compound of momelotinib, revealed anemia response rate of 36% in patients with a baseline hemoglobin level ≤10 g/dl, with 2 of 6 transfusiondependent patients becoming transfusion-independent after treatment. 23,24 The current study suggests that patients with post-ET MF and those with a lower pre-treatment serum ferritin value were more likely to show an anemia response to momelotinib therapy. In this regard, it is to be noted that transfusion burden was also independently correlated with anemia response in transfusion-dependent patients and in those with hemoglobin <10 g/dl but did not account for the impact of serum ferritin (Table 2).…”
Section: Discussionmentioning
confidence: 67%
“…In the current issue of AJH , Zhang and colleagues from China present results from a phase‐2 multicenter study of jaktinib, in dynamic international prognostic scoring system (DIPSS)‐plus high/intermediate risk MF (NCT03886415) 9 . The study included 104 patients randomized to jaktinib 100 mg twice‐daily or 200 mg once‐daily, with additional 14 patients enrolled to the 100 twice‐daily cohort.…”
Section: Drug Ruxolitinib Fedratinib Pacritinib Momelotinib Jaktinibmentioning
confidence: 99%
“…Limitations of the above-described study by Zhang et al 9 include lack of laboratory correlative studies, especially in terms of mutation information, underrepresentation of DIPSS-plus high-risk and transfusion-dependent patients at baseline, which is further confounded by regional transfusion practices, and the need for longerterm follow-up to accurately assess treatment-emergent neuropathy, which is known to be prevalent in patients treated with momelotinib. 12 These limitations, however, do not undermine the key observations of more than trivial anemia response and the possible influence of dosing schedule on both rates of response and AEs.…”
mentioning
confidence: 99%
See 1 more Smart Citation